Post-transcriptional Inhibition of Hsc70-4/HSPA8 Expression Leads to Synaptic Vesicle Cycling Defects in Multiple Models of ALS. - Coyne, A.N.; Lorenzini, I.; Chou, C.C.; Torvund, M.; Rogers, R.S.; Starr, A.; Zaepfel, B.L.; Levy, J.; Johannesmeyer, J.; Schwartz, J.C.; Nishimune, H.; Zinsmaier, K.; et al. (Cell reports, 2017)
Amyotrophic lateral sclerosis (ALS) is a synaptopathy accompanied by the presence of cytoplasmic aggregates containing TDP-43, an RNA-binding protein linked to ?97% of ALS cases. Using a Drosophila model of ALS, we show that TDP-43 overexpression (OE) in motor neurons results in decreased expression of the Hsc70-4 chaperone at the neuromuscular junction (NMJ). Mechanistically, mutant TDP-43 sequesters hsc70-4 mRNA and impairs its translation. Expression of the Hsc70-4 ortholog, HSPA8, is also reduced in primary motor neurons and NMJs of mice expressing mutant TDP-43. Electrophysiology, imaging, and genetic interaction experiments reveal TDP-43-dependent defects in synaptic vesicle endocytosis. These deficits can be partially restored by OE of Hsc70-4, cysteine-string protein (Csp), or dynamin. This suggests that TDP-43 toxicity results in part from impaired activity of the synaptic CSP/Hsc70 chaperone complex impacting dynamin function. Finally, Hsc70-4/HSPA8 expression is also post-transcriptionally reduced in fly and human induced pluripotent stem cell (iPSC) C9orf72 models, suggesting a common disease pathomechanism.